2015
DOI: 10.1002/lary.25143
|View full text |Cite
|
Sign up to set email alerts
|

Low‐cost modular phonosurgery training station: Development and validation

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 11 publications
2
25
0
Order By: Relevance
“…The simulator demonstrated both face and transfer validity and the participants reported a significant increase in the level of comfort post workshop. A low cost phonosurgery simulator described by Holliday et al () demonstrated face, construct, and content validity. Fleming et al () describe a high fidelity microlaryngoscopy simulator that can be used for the assessment of microlaryngoscopy skills in an immersive environment and has been shown to have face and transfer validity.…”
Section: Bench Modelsmentioning
confidence: 99%
“…The simulator demonstrated both face and transfer validity and the participants reported a significant increase in the level of comfort post workshop. A low cost phonosurgery simulator described by Holliday et al () demonstrated face, construct, and content validity. Fleming et al () describe a high fidelity microlaryngoscopy simulator that can be used for the assessment of microlaryngoscopy skills in an immersive environment and has been shown to have face and transfer validity.…”
Section: Bench Modelsmentioning
confidence: 99%
“…There are several simulators for airway and laryngology, including biologic tissue (porcine or ovine models) and nonbiologic training models [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. These models have been used for intubation skills and removal of airway foreign body as well as microlaryngoscopic procedures.…”
Section: Airway and Throat Simulatorsmentioning
confidence: 99%
“…The layered structure of the vocal fold should be infringed as little as possible. All these single-operator procedures require acquisition of necessary skills and perfect technique [14]. Simultaneously, thorough knowledge of vocal fold The vocal fold epithelial cells, the connective and muscle fibers, and even the blood vessels run longitudinally, which is parallel to the vocal fold free edge.…”
Section: Streszczeniementioning
confidence: 99%